Vólvulo de ciego con lesión de colon ascendente: Alternativa de tratamiento - Brito Sosa, Germán; Iraizoz Barrios, Ana María (My University, 2021)
Cecal volvulus is a rare disease responsible for 1% of the cases of intestinal occlusion, whose main etiology is due to a mobile cecum. A 73-year-old male patient with a history of constipation is presented. He had a clinical picture of abdominal pain and distention, nausea, vomiting, and absence of stool or gas expulsion. A Cecal volvulus with lesion in the ascending colon was found. The surgical technique most frequently performed by surgeons for cecal volvulus is right hemicolectomy with transverse ileus anastomosis, but if the volvulus caused intestinal necrosis and the patient is hemodynamically unstable, it is safer to perform intestinal resection and ileostomy. Ascending ileus anastomosis performed at a higher level of the ascending colon is a safe alternative for the restitution of intestinal transit in patients with cecal volvulus.
El vólvulo de ciego es una enfermedad poco frecuente y responsable del 1% de los casos de oclusión intestinal, cuya principal etiología está dada por un ciego móvil. Se presenta un paciente varón de 73 años, con antecedente de estreñimiento. Presenta cuadro clínico de dolor y distensión abdominal, náuseas, vómitos y ausencia de expulsión tanto de heces como de gases. Se halló vólvulo de ciego con lesión en colon ascendente. La técnica quirúrgica que los cirujanos realizan con más frecuencia en el vólvulo de ciego es la hemicolectomía derecha con íleo transverso anastomosis, pero si el vólvulo causó necrosis intestinal y el paciente se encuentra hemodinámicamente inestable, es más seguro realizar la resección intestinal e ileostomía. La íleo ascendente anastomosis realizada a un nivel más alto del colon ascendente es una alternativa segura para la restitución del tránsito intestinal en los pacientes con vólvulos de ciego.
Keywords: ENFERMEDADES DEL CIEGO; VOLVULO INTESTINAL; DOLOR ABDOMINAL; OBSTRUCCION INTESTINAL; ANASTOMOSIS QUIRURGICA